An Analysis Of Semantic On Onang-Onang Of Angkola-Mandailing Wedding Ceremony - Harahap, Mastika Sari (Universitas Muhammadiyah Sumatera Utara, 2021)
This research was intended to find out the lexical relations in onang-onang lyrics of Angkola-Mandailing wedding ceremony. The methodology this research used descriptive qualitative method. The collecting data of this research are suitable the supported and criteria of the research. This research classified to seven types such as synonymy, antonymy, polysemy, hypernym, hyponymy and meronymy to found out the most dominant types of lexical relations in onang-onang lyrics in Angkola-Mandailing wedding ceremony. Finally, it was found that 5 datas of synonyms, 12 datas of antonymy, 5 datas of polysemy, 6 datas of hyponymy, 7 datas of homonym, and 10 of meronymy. Therefore, the writer found the most dominant types of lexical relations of this research was 12 of antonomy from 51 case total.